Labour protests during the pandemic: The case of hospital and retail workers in 90 countries - Vera Trapmann; Charles Umney; Denis Neumann; Simon Joyce; Ioulia Bessa (International Labour Organization (ILO), 2022)
With a novel methodology searching news events from world's largest news agencies via the online GDELT project, this report documents protest of key workers against their working conditions during the COVID-19 pandemic in 90 countries. The report offers the first global dataset of labour protests of key workers during the pandemic. It focusses on two sectors, healthcare and retail. The results show that, overall, despite large volumes of protest over acute COVID-related problems such as the provision of Personal Protective Equipment (PPE), the main concern of protesting workers during the pandemic was their pay. Collective action accompanying demands for pay rises involved not only the withdrawal of labour, but also demonstrations and leverage tactics. Health and safety was the second most important concern, and protests linked to these demands did not cease when the pandemic became less deadly. Protest spiked during the initial March 2020 lockdowns, before continuing at a lower level throughout the pandemic. The report identifies important variation between countries and sectors, and highlights specific local contingencies, and strategic decisions taken by workers and their unions. To this end, the report also analyses in more detail five countries where protest was particularly important: France, India, Nigeria, the United States, and Argentina. The report offers a first step to understanding the variety of labour protests beyond more institutionalised forms of collective voice. It will be important to study further the relation between informal forms of protest action and institutionalised gains, during and beyond COVID-19.
Keywords: 330